A new insight into the accident investigation: A case study of Tianjin Port fire and explosion in China. Issue 4 (8th April 2017) - Aitao, Zhou; Lingpeng, Fan
Abstract : By figuring out the cause and learning the lessons, accident investigation serves to avoid the like accidents effectively. Incident Management is one of the twelve key factors among China's process safety management system (PSMS), while accident investigation is central to Incident Management. This paper selected "Tianjin Port 8.12 fire and explosion accident" ("Tianjin 8.12 Accident") as an investigation case. Three core components: cause analysis, affixing the responsibility and corrective suggestions, were unfolded. Problems were analyzed from process safety and accident development point of view. A process analysis approach, which is based on event sequence‐barrier failed, was employed for accident investigation. Affixing responsibility process based on failed analysis was used for accident investigating and affixing. In order to give corrective suggestions, safety information‐based corrective suggestions are proposed by starting from systematic and interconnected perspective and combining with finding failed behaviors and an in‐depth analysis of the causes behind the behaviors. Subsequently, an integral accident investigation approach, which consists of cause analysis based on event sequence‐barrier failed, affixing responsibility process based on failed analysis and systematic corrective measures based on safety information, can effectively render scientific theoretical guidance to investigation and analysis of an accident. © 2017 American Institute of Chemical Engineers Process Saf Prog 36: 362–367, 2017